Syntrichia laevipila Brid., a Bryophyta from Northwest Argentina as a Source of Antioxidants and Antimicrobials - Luis Ignacio Jiménez; Florencia Maria Correa Uriburu; José Javier Martínez Chamás; Guillermo Martin Suárez; Iris Catiana Zampini; Mario J. Simirgiotis; María Inés Isla (Plants)
In recent years, numerous studies have emerged on the biological activities of bryophytes and their potential for therapeutic use. However, mosses appear to be a relatively overlooked group. The objective of this study was to conduct a phytochemical analysis of one hydroalcoholic extract of Syntrichia laevipila and to evaluate its potential as an antioxidant and antimicrobial agent. The moss was collected in the Chaco Serrano region of Argentina, specifically on Jacaranda mimosifolia, and subsequently extracted by maceration in ethanol/water. UHPLC/ESI/MS/MS analysis identified 32 peaks, including phenolic compounds (phenolic acids, lignans, chalcones, and flavonoids) and non-hydrophilic compounds (terpenoids, fatty acids, and brassinosteroids). Maslinic and oleanolic acids, two triterpenoids present in S. laevipila, were also detected in J. mimosifolia, a substrate of this moss. The concentration of phenolic compounds was 19.05 ± 0.21 µg GAE/mL, while the total flavonoid concentration was 13.13 ± 0.33 µg QE/mL. The determination of reducing and total sugars yielded 0.22 ± 0.03 mg GE/mL and 1.26 ± 0.24 mg GE/mL, respectively, while the concentration of soluble proteins was 90.60 ± 4.50 µg BSAE/mL. The extract exhibited antioxidant properties by scavenging ABTS•+, H2O2, AAPH, and HO• radicals. Additionally, it demonstrated antibacterial activity by inhibiting the growth of four strains of Staphylococcus aureus. The data obtained suggest that the hydroalcoholic extract of S. laevipila possesses significant potential as a natural antioxidant and antimicrobial agent, making it a promising candidate for the development of phytotherapeutic and cosmetic products.